Whole‐Plant Manual and Image‐Based Phenotyping in Controlled Environments. Issue 1 (3rd March 2017) - Agnew, Erica; Bray, Adam; Floro, Eric; Ellis, Nate; Gierer, John; Lizárraga, César; O'Brien, Darren; Wiechert, Madeline; Mockler, Todd C.; Shakoor, Nadia; Topp, Christopher N.
Abstract: Phenotypic measurements and images of crops grown under controlled‐environment conditions can be analyzed to compare plant growth and other phenotypes from diverse varieties. Those demonstrating the most favorable phenotypic traits can then be used for crop improvement strategies. This article details a protocol for image‐based root and shoot phenotyping of plants grown in the greenhouse to compare traits among different varieties. Diverse maize lines were grown in the greenhouse in large 8‐gallon treepots in a clay granule substrate. Replicates of each line were harvested at 4 weeks, 6 weeks, and 8 weeks after planting to capture developmental information. Whole‐plant phenotypes include biomass accumulation, ontogeny, architecture, and photosynthetic efficiency of leaves. Image analysis was used to measure leaf surface area and tassel size and to extract shape variance information from complex 3D root architectures. Notably, this framework is extensible to any number of above‐ or below‐ground phenotypes, both morphological and physiological. © 2017 by John Wiley & Sons, Inc.